2021
DOI: 10.1186/s40635-020-00367-3
|View full text |Cite
|
Sign up to set email alerts
|

Lung ultrasound and computed tomography to monitor COVID-19 pneumonia in critically ill patients: a two-center prospective cohort study

Abstract: Background Lung ultrasound can adequately monitor disease severity in pneumonia and acute respiratory distress syndrome. We hypothesize lung ultrasound can adequately monitor COVID-19 pneumonia in critically ill patients. Methods Adult patients with COVID-19 pneumonia admitted to the intensive care unit of two academic hospitals who underwent a 12-zone lung ultrasound and a chest CT examination were included. Baseline characteristics, and outcomes … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
29
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 43 publications
5
29
0
2
Order By: Relevance
“…They reported that the LUS findings they reached in their study included pleural line and B line abnormalities, similar to the results of other studies [19]. In the study using the same number of examination zones in intensive care patients, the correlation between LUS scores and CT scores was 0.87, and it was found that there was a good degree of agreement [20]. In addition, they reported that the LUS, in which six zones were examined, was able to yield similar results to the LUS, in which twelvezones were evaluated.Despite the fact that the results needed to be confirmed, they stated that the results were similar to the literature data, and the results of the studies using the BLUE protocol [20].…”
Section: A C C E P T E D a R T I C L Esupporting
confidence: 81%
See 1 more Smart Citation
“…They reported that the LUS findings they reached in their study included pleural line and B line abnormalities, similar to the results of other studies [19]. In the study using the same number of examination zones in intensive care patients, the correlation between LUS scores and CT scores was 0.87, and it was found that there was a good degree of agreement [20]. In addition, they reported that the LUS, in which six zones were examined, was able to yield similar results to the LUS, in which twelvezones were evaluated.Despite the fact that the results needed to be confirmed, they stated that the results were similar to the literature data, and the results of the studies using the BLUE protocol [20].…”
Section: A C C E P T E D a R T I C L Esupporting
confidence: 81%
“…In the study using the same number of examination zones in intensive care patients, the correlation between LUS scores and CT scores was 0.87, and it was found that there was a good degree of agreement [20]. In addition, they reported that the LUS, in which six zones were examined, was able to yield similar results to the LUS, in which twelvezones were evaluated.Despite the fact that the results needed to be confirmed, they stated that the results were similar to the literature data, and the results of the studies using the BLUE protocol [20]. Since there were studies in the literature using different methods of examination, Soldati et al created a LUS protocol with the aim of developing international standardization.…”
Section: A C C E P T E D a R T I C L Ementioning
confidence: 91%
“…First, whether the reference standard accurately represents total pulmonary involvement is uncertain. In fact, previous research has shown equivalence of both 6- or 12-zone protocols compared to gold standard chest computed tomography (CT) [ 3 , 4 ]. Second, the 14-zone protocol’s overrepresentation of posterior zones (43%) constitutes a scan-location bias, which is problematic when examining disease with gravity-dependent distribution.…”
mentioning
confidence: 99%
“…Reference test was a 12-zone LUS protocol which has shown to have monitoring equivalence to CT and index test was a 6-zone LUS protocol (Fig. 1 A) [ 4 ]. Each LUS zone was scored from 0 (A-pattern) to 3 (consolidation).…”
mentioning
confidence: 99%
“…(5) Several studies have shown that LUS can detect interstitial disease, subpleural consolidations, and respiratory distress of any aetiology, with sensitivity and specificity superior to chest radiography and comparable to CT. (6)(7)(8) Indeed, LUS has already been recommended in past viral pandemics (9) and growing evidence demonstrates its effectiveness in patients with COVID-19, (10) which allows identifying the degree of lung involvement, its course, and the possible association between the initial lung involvement and its prognosis. (11)(12)(13)(14)(15) Our objective was to evaluate the performance of LUS through the lung ultrasound score (LUS score) to determine the severity of pneumonia and the short-term outcomes of patients with COVID-19 admitted to the intensive care unit. We hypothesize that the Lung Ultrasound Score (LUS) correlates with clinical evolution and predicts mortality in critically ill COVID-19 pneumonia patients.…”
Section: Introductionmentioning
confidence: 99%